L’Approche opératoire du développement personnel et vocationnel: ses fondements et ses valeurs - Pelletier, Denis (Canadian Journal of Counselling and Psychotherapy, 2012)
The functional approach concerns the processes underlying vocational and personal development, and the way we can activate these processes. Psychological development has an existential meaning of searching for. The quest for identity andthe movement toward self-actualization are functionally processes of discovery like exploration, crystallization, specification and implementation. Specific abilities and attitudes make possible the exercise of each of these processes. Creative thinking is involved in exploration, conceptual thinking in crystallization, evaluative thinking in specification, and implicative thinking in implementation.This theoretical model and the empirical results supporting it have many implications for counselling and psychological education.